Lama Waktu Kontak Minyak Jeruk (Citrus sinensis) sebagai Hand Sanitizer terhadap Penurunan Angka Kuman Telapak Tangan - Hana Yesica Surbakti; Choirul Amri; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2020)
Based on one earlier research, hand sanitizer made of citrus oil at 40% concentration, after 15 minutes of usage was able to decrease the number of hands germ up to 80%. However, among the observed replications, the reductions were not significantly different. Therefore, a following study must be conducted to know whether among 20 minute, 40 minute and 60 minute contact times have different effectiveness. The research method was quasi experiment with time series design. The sampling of germ number was taken from the palms of six food handlers of the canteen of Poltekkes Yogyakarta, and then the examinations were held in BBTKLPP Yogyakar-ta. The data were analysed by using Kruskal-Wallis test at 0,05 level of significance. The study results show that the highest average reduction of germ number was from 40 minute contact time, i.e. 80%; and the lowest was from both 20 minute and 60 minute, i.e. 50%. The p-value gained was 0,434; which means that the reduction differences were not statistically significant. Nonetheless, descriptively, it can be seen that the most effective contact time of hand sanitizer made of citrus oil is 40 minutes.